The Production and Use of Evidence in Health Care Service Innovation: A Qualitative Study. (March 2013) - Vasileiou, Konstantina; Barnett, Julie; Young, Terry
The focus of this article is on a range of concepts of evidence employed by health care innovators in pursuing service innovations and in demonstrating their success. In-depth, semi-structured interviews were conducted with 18 key informants in the United Kingdom who had won Health Service Journal awards for successfully implementing 15 service innovations. Four concepts of evidence were identified: (a) evidence of effectiveness—both direct and indirect, (b) evidence of efficiency, (c) evidence of innovation acceptance, and (d) evidence of relevance. The results suggest that the innovators articulated evidential concepts from the main approaches prevailing in the British National Health Service, namely clinical trials and improvement cycles. Most aspired to "better" evidence than they were able to obtain, while the approach to evidence gathering was very pragmatic and was more aligned with the improvement-cycle framework. Developing supporting mechanisms for assisting innovation evaluation is an important challenge if service innovation is to be routinely attempted and achieved in health care.